miR-200c regulation of metastases in ovarian cancer: Potential role in epithelial and mesenchymal transition - Siti Aishah Sulaiman; Nurul-Syakima Ab Mutalib; Rahman Jamal (Frontiers Media S.A., 2016)
Among the gynecological malignancies, ovarian cancer is the most fatal due to its high mortality rate. Most of the identified cases are epithelial ovarian cancer (EOC) with five distinct subtypes: high-grade serous carcinoma, low-grade serous carcinoma, mucinous carcinoma, endometrioid carcinoma and clear-cell carcinoma. Lack of an early diagnostic approach, high incidence of tumor relapse and the heterogenous characteristics between each EOC subtypes contribute to the difficulties in developing precise intervention and therapy for the patients. MicroRNAs (miRNAs) are single-stranded RNAs that have been shown to function as tumor suppressors or oncomiRs. The miR-200 family, especially miR-200c, has been shown to be implicated in the metastasis and invasion of ovarian carcinoma due to its functional regulation of epithelial-to-mesenchymal transition (EMT). This mini review is aimed to summarize the recent findings of the miR-200c functional role as well as its validated targets in the metastasis cascade of ovarian cancer, with a focus on EMT regulation. The potential of this miRNA in early diagnosis and its dual expression status are also discussed.